Manajemen Pelaksanaan Biro Jodoh Online dalam Tinjauan Kaidah Dharurah - Nasrullah, Nasrullah; Noor, Al Mujahidin (Attractive : Innovative Education Journal, 2022)
This paper aims to explain the phenomenon of the practice of finding a life partner through the use of online dating agency sites when analyzed by applying emergency rules. The results of the study show that preferences for online matchmaking agencies can be regarded as a complementary tool in finding a life partner, meaning that under any circumstances the majority in finding a partner prefer to utilize the services of their parents, siblings or friends. So that this online dating agency is not used as the main tool in finding a life partner, but as a complementary tool to open the gate to a more serious stage. If it is related to the theory in emergency rules, the use of an online dating agency is not considered an emergency. And it will be dharurat if there are reasons that can be justified according to Sya'i law, including being used for work reasons and busy activities so there is no time and opportunity to find a life partner. The age of marriage is sufficient, even beyond the ideal age, but you have not yet found a match or there may not be someone suitable, so an alternative online dating agency can be used as an alternative medium. Not a few people get life partners through online dating agencies, meaning that the positive impact of this media for some people is a solution to ending their single life, aka loneliness, although it is realized that there are online dating agencies that are mischievous. Keywords: Life Partner, Online Dating, Emergency Rules